Case Report: Series report and literature review on postoperative subdural hygroma complications following biportal endoscopic spinal surgery - Bai, Guangchao; Wei, Guojun; Jian, Yongzhi; Jing, Xiaowei; Hu, Qingfeng (Frontiers in Surgery, 2025)
BackgroundBiportal Endoscopic Spinal Surgery (BESS) is a minimally invasive technique that has gained popularity for performing spinal procedures, including discectomy, decompression, and interbody fusion, in the cervical, thoracic, and lumbar regions. Whilst dural tears, epidural haematoma and transient paresthesia are well-documented complications associated with BESS, cases of subdural hygroma remain exceedingly rare. The present study presents a case series of three patients who developed postoperative subdural hygroma following BESS. An accompanying literature review was conducted in order to explore potential mechanisms and management strategies.Case presentationThe initial case pertained to a 35-year-old male patient who underwent a cervical discectomy and foraminal decompression via BESS for the treatment of cervical spondylosis. Subsequently, the patient developed a cranial subdural hygroma. The second patient, a 53-year-old male, underwent a lumbar discectomy and decompression via BESS for lumbar disc herniation with concomitant spinal stenosis. Postoperative imaging revealed extensive lumbar subdural hygroma. The third case report concerns a 74-year-old male patient who underwent BESS decompression surgery for lumbar spinal stenosis. Postoperatively, the patient developed a subdural hygroma in the lower lumbar region.ConclusionThe development of subdural hygroma following BESS may be attributed to a combination of factors, including occult dural tears, abrupt alterations in intraspinal pressure, and ischemia-reperfusion injury. In view of the potential clinical implications of this rare complication, greater awareness and monitoring is warranted in the postoperative management of patients undergoing BESS.